PENGARUH MODEL INKUIRI TERBIMBING TERHADAP LITERASI SAINS SISWA PADA MATERI PERUBAHAN LINGKUNGAN KELAS X SMA NEGERI 1 PERCUT SEI TUAN - Lubis, Rizka; Widia Ningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of guided inquiry model on students' scientific literacy skills on environmental change material in class X of SMA Negeri 1 Percut Sei Tuan. The research method used is a quasi-experimental with a non-equivalent control group design. The study population was all students of class X, with samples of class X-1 as the experiment and X-3 as the control through purposive sampling technique. Scientific literacy data were collected through a test based on the PISA 2025 framework that includes aspects of competency, context, and content. Data analysis was carried out through the Independent Samples t-Test and N-Gain test. The results showed a significant effect of the guided inquiry model on students' scientific literacy, with the average post-test score of the experimental class being higher than the control class. The increase in scientific literacy in the experimental class was in the moderate category (N-gain 0.39), while the control class was in the low category (N-gain 0.17). The application of guided inquiry has been proven to be effective in facilitating students to build conceptual understanding through scientific investigations, linking knowledge to environmental problems, and improving overall scientific literacy skills. This model is recommended as an alternative learning method to strengthen students' scientific literacy in the 21st century.